Eagles : Talons of Eagles - Book 3 - Johnstone, William W. (New York : Kensington, 1996)
In the middle of the Civil War, Jamie MacCallister, a 50- year-old retired gunfighter from Colorado is offered work by both President Lincoln and General Robert E. Lee. Although MacCallister is anti-slavery, he is even more pro -states rights and signs on with the Confederacy to become a guerrilla commander. By the author of Eyes of Eagles.
"A Pinnacle Book".
Keywords: MacCallister, Jamie Ian (Fictitious character) -- Fiction; United States -- History -- Civil War, 1861-1865; Fiction; Western stories; War stories